Short Note on Topological Fuzzy Spaces of the Behaviour of GSïƒ™ fuzzy Closed Sets - Mary Victoria Florence, M.; Priyadarshini, E.; Vidhya, M.; Govindarajan, A.; P.Siva, E. (International Journal of Engineering and Technology, 2018)
Many fuzzy topologists have very good interest in generalized fuzzy closed sets and in fuzzy point set topology. Here, properties of GS ïƒ™ in fuzzy topological spaces and its relationship with other generalized fuzzy closed sets has been discussed.Â